Prophylactic VA-ECMO During Complex High-Risk PCI - Chenliang Pan, MD; Youqi Zhu, MD; Jing Zhao, MD; Bo Zhang, MD; Sixiong Hu, MD; Cunrui Zhao, MD; Xiaoxue Meng, MD; Xinghu Zhou, MD; Yurun Su, MD; Erkun Xing, MM; Peng Lei, MD; Nan Bai, MD; et al. (JACC: Advances)
Background: Evidence on prophylactic venoarterial extracorporeal membrane oxygenation (VA-ECMO) during elective percutaneous coronary intervention (PCI) in patients with complex high-risk coronary artery lesions is limited. Objectives: The authors aimed to assess the safety and effectiveness of prophylactic VA-ECMO during PCI. Methods: This single-center, randomized trial enrolled 70 patients with complex high-risk coronary lesions (Synergy Between PCI with Taxus and Cardiac Surgery [SYNTAX] score ≥33) who declined coronary artery bypass grafting. Patients were divided into those who had prophylactic VA-ECMO (n = 34) prior to PCI and controls who did not have prophylactic VA-ECMO (n = 36). Elective PCI was performed, and complications were recorded. Life-threatening complications included: 1) cardiac arrest unresponsive to cardiopulmonary resuscitation; 2) cardiogenic shock; 3) acute left heart failure unresponsive to therapy; and 4) refractory malignant arrhythmias. SYNTAX scores pre- and post-PCI were calculated. The primary endpoints were the rate of complications during PCI and SYNTAX score reduction post-PCI. Results: Between June 2021 and August 2023, 70 patients (women: 14.3%) underwent PCI. SYNTAX scores in the VA-ECMO and control group were similar (37.8 [34.5-44.0] vs 35.8 [33.2-40.8], P = 0.11). Life-threatening complications were lower in the VA-ECMO group compared to controls (0% vs 19.4%; P = 0.01). Emergency VA-ECMO was required in 19.4% of the control group. The VA-ECMO group showed greater absolute reduction in SYNTAX scores (27.2 [24.5-35.0] vs 22.5 [11.5-32.8], P = 0.04). Conclusions: In this single-center study of patients undergoing elective PCI of complex high-risk coronary lesions, prophylactic VA-ECMO was associated with lower rates of life-threatening complications and larger reduction in SYNTAX scores. Larger studies are needed to further define optimal management strategies in high-risk complex PCI.